Answer:
x = 6
Step-by-step explanation:
The midsegment of a trapezoid is the line parallel to the parallel sides of the trapezoid, which connects the midpoints of the non-parallel sides.
The length of the midsegment of the trapezoid is half the sum of the length of the parallel sides.
i.e,
Length of the midsegment = (1/2) *(Length of base1 + Length of base2)
6x - 24 = (1/2) * (5 + 2x + 7)
12x - 48 = 2x + 12
10x = 60
x=6
∴ x = 6
Answer:
(8x - 5y)(8x + 5y)
Step-by-step explanation:
To factor the expression, use the difference of squares pattern. A difference of squares is subtraction between two perfect squares and factors as a² - b² = (a-b)(a+b).
The expression has the perfect squares 64x² and 25y². Take the square root of each. The factors become (8x - 5y)(8x + 5y).
Answer:
false
Step-by-step explanation:
3/5 is 60%